2021
DOI: 10.1007/s00167-021-06640-6
|View full text |Cite
|
Sign up to set email alerts
|

Superb microvascular imaging (SMI) detects increased vascularity of the torn anterior cruciate ligament

Abstract: PurposeUltrasound with superb microvascular imaging (SMI) is a novel microvascular imaging technology which may be useful to assess the vascularity of the torn anterior cruciate ligament (ACL) as a potential measure of healing potential following surgery. This study aimed to quantify the vascularity of the torn and intact ACL using ultrasound with SMI. Methods23 patients (mean age ± standard deviation, 27.1 ± 12.8 years), who were diagnosed with an ACL tear with an intact contralateral ACL were enrolled (ACL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“…Specifically, in situ QT thickness as measured on preoperative US was the most predictive of intraoperative QT graft diameter size. These findings are similar to a previous retrospective study that found moderate to strong correlation between the intraoperative diameter of the QT autograft and the in situ QT thickness and CSA [41]. However, to assess the actual predictive ability of both modalities, a prospective study was needed.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Specifically, in situ QT thickness as measured on preoperative US was the most predictive of intraoperative QT graft diameter size. These findings are similar to a previous retrospective study that found moderate to strong correlation between the intraoperative diameter of the QT autograft and the in situ QT thickness and CSA [41]. However, to assess the actual predictive ability of both modalities, a prospective study was needed.…”
Section: Discussionsupporting
confidence: 87%
“…Preoperative MRI was performed with a standardized protocol for ACL injury using a 1.5 T open‐bore magnet (GE Signa, GE Healthcare, Chicago, Illinois, USA). All assessments using preoperative MRI were performed based on a previously validated protocol [41]. The maximum QT thickness at 15 mm proximal to the superior pole of the patella was assessed on a T2‐weighted sagittal image (MRI thickness at 15 mm) (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SMI may be used to improve the diagnostic accuracy of low-grade digital collateral ligament injuries where there may not be a clear disruption in the ligament substance. Early research on grading of vascularity using SMI in the musculoskeletal system 12,13 has already seen promising results, and with improvements in the technology and conducting similar studies in the hand, it may be possible to stratify and grade injuries to smaller ligaments such as DCL injuries. There are two important limitations to the usage of this technology.…”
Section: Discussionmentioning
confidence: 99%